The Effects of Propofol on a Human in vitro Blood-Brain Barrier Model - Hughes, Jason M.; Neese, Olivia R.; Bieber, Dylan D.; Lewis, Kirsten A.; Ahmadi, Layla M.; Parsons, Dustin W.; Canfield, Scott G. (Frontiers in Cellular Neuroscience, 2022)
Background Recently, the safety of repeated and lengthy anesthesia administration has been called into question, a subset of these animal studies demonstrated that anesthetics induced blood-brain barrier (BBB) dysfunction. The BBB is critical in protecting the brain parenchyma from the surrounding micro-vasculature. BBB breakdown and dysfunction has been observed in several neurodegenerative diseases and may contribute to both the initiation and the progression of the disease. In this study we utilize a human induced pluripotent stem cell (iPSC) derived-BBB model, exhibiting near in vivo properties, to evaluate the effects of anesthetics on critical barrier properties. Methods iPSC-derived brain microvascular endothelial cells (BMECs) expressed near in vivo barrier tightness assessed by trans-endothelial electrical resistance and para-cellular permeability. Efflux transporter activity was determined by substrate transport in the presence of specific inhibitors. Trans-cellular transport was measured utilizing large fluorescently tagged dextran. Tight junction localization in BMECs was evaluated with fluorescent microscopy. The anesthetic, propofol was exposed to BMECs at varying durations and concentrations and BBB properties were monitored post-exposure. Results Following propofol exposure, BMECs displayed reduced resistance and increased permeability indicative of a leaky barrier. Reduced barrier tightness and the dysregulation of occludin, a tight junction protein, were partly the result of an elevation in matrix metalloproteinase (MMP) levels. Efflux transporter activity and trans-cellular transport were unaffected by propofol exposure. Propofol induced barrier dysfunction was partially restored following matrix metalloproteinase inhibition. Conclusion For the first time, we have demonstrated that propofol alters BBB integrity utilizing a human in vitro BBB model that displays key in vivo characteristics. A leaky BBB enables otherwise impermeable molecules such as pathogens and toxins the ability to reach vulnerable cell types of the brain parenchyma. A robust human in vitro BBB model will allow for the evaluation of several anesthetics at fluctuating clinical scenarios and to elucidate mechanisms with the goal of ultimately improving anesthesia safety.